E-commerce and Digital Literacy of UMKM in Madiun Regency during the COVID-19 - Selfia Bintariningtyas; Tri Mulyaningsih; Lely Ratwianingsih (Universitas Merdeka Madiun, 2021)
Abstract—The purpose of this research is to find out the role of E-commerce and digital literacy of micro, small and medium-sized enterprises (UMKM) in Madiun district in helping the sale of their products during the covid-19 pandemic. This research is expected to help increase the participation of UMKM. This study uses qualitative descriptive research method with the population of UMKM in Madiun. The determination of samples in this study by the purposive sampling method. The data From 100 respondents was collected by field observation and supported by the dissemination of questionnaires. The collected data is analyzed descriptively-qualitatively. From the results of the analysis obtained that 71% of respondents can use and operate digital devices properly and use digital devices every day in daily life even during the Covid-19 pandemic. This shows that most actors UMKM has good digital literacy. Some of the respondents do sales or promotion of their products by not using E-commerce facilities but are more likely to use through direct sales that is offline. A total of 53% of respondents used E-commerce to help sales of their products and said that E-commerce helped UMKM during the Covid-19 pandemic.